GUIDED BONE REGENERATION IN RECONSTRUCTION OF BONE DEFECTS - Gjorgjievski, Pavle; Papakoca, Kiro; Markovska Arsovska, Mirjana; Dimova, Cena; Temelkova, Simona; Chadikovska, Elizabeta (Journal of Morphological Sciences; Vol 7 No 1 (2024): JMS, 2024)
Guided bone regeneration (GBR) is a bone graft procedure that uses a covering barrier membrane to block soft tissue invasion. Bone reconstruction for implant placement and for preparation for prosthetic restorations  varies in numerous techniques and materials, each of them bringing advantages and specific qualities for different types of bone defects. The case report present an efficient method of GBR by sticky bone which is obtained by mixing PRF and bone graft together supported by PRF membrane. During the regular controls, no big swelling was seen, the patient did not complain of pain. The postoperative course was without complications. Keywords: PRF, guided bone regeneration, bone defect, sticky bone, PRF membrane